2012
DOI: 10.1553/sunda2009_2010ssi_2010_s31
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures in the Life Zones of the Tyrolean Alps

Abstract: The bioclimatic temperatures that mountain plants experience are very different from the macroclimatic temperatures and vary according to the exposition, relief, and growth form. This is shown in the example of boundary layer temperatures recorded in the Tyrolean Alps between the timberline and the nival zone over several years. Microsite temperatures were compared to the air temperatures provided by meteorological stations of the official weather service nearby.In winter plant temperatures below the snow are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Height aboveground and aspect are of primary importance and during the day they override the effect of the 300 m elevational difference between the lower and higher sites, in agreement with Diemer (1996). The typical daytime vertical temperature profile, with a narrow boundary layer of warm air above heated topsoil and overlaid with cooler air (Geiger, 1965;Meinzer et al, 1994a;Jordan and Smith, 1995;Larcher and Wagner, 2011), was observed only on the leeward, western side. On the windward, eastern side, low radiation input along with very high air humidity due to permanent cloudiness (Sklenář et al, 2015) produced very gentle vertical temperature profiles that lacked the layer of substantially warmer air near the ground.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Height aboveground and aspect are of primary importance and during the day they override the effect of the 300 m elevational difference between the lower and higher sites, in agreement with Diemer (1996). The typical daytime vertical temperature profile, with a narrow boundary layer of warm air above heated topsoil and overlaid with cooler air (Geiger, 1965;Meinzer et al, 1994a;Jordan and Smith, 1995;Larcher and Wagner, 2011), was observed only on the leeward, western side. On the windward, eastern side, low radiation input along with very high air humidity due to permanent cloudiness (Sklenář et al, 2015) produced very gentle vertical temperature profiles that lacked the layer of substantially warmer air near the ground.…”
Section: Discussionsupporting
confidence: 61%
“…The two sites were about 200 elevational meters below the distributional limit of Azorella on the Antisana volcano, which suggests that the uppermost cushion plants might grow at even lower mean temperatures. In contrast, Saxifraga bryoides, a cushion plant from a glacier foreland (2880 m) in the Austrian Alps experienced a mean temperature of 8.5 °C during 105 days of the temperate alpine growing season (Larcher and Wagner, 2011;Larcher, 2012). This difference suggests that the growing season mean temperature correlated with the occurrence of alpine treelines worldwide (Körner, 2003;Körn-er and Paulsen, 2004;Scherrer and Körner, 2011) may not be easily applicable to explain upper distributional limits of alpine plant growth forms, at least in the tropics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some of them belong to specialized life forms, for instance, cushions that accumulate heat [15,29], e.g., Saxifraga bryoides and S. oppositifolia. Physiological and morphological adaptations of the cold-specialized species, particularly in the leaves, enable efficient gas exchange in cold environment [15,30], but are disadvantageous in the warmer climate and cause overheating and withering of plants that cannot tolerate the increase of temperature above certain levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many alpine plant species have evolved prostrate growth forms that promote the decoupling of plant body temperature from ambient air (Körner & Larcher 1988) in response to the decrease in mean air temperature with increasing elevation. This decoupling allows canopy temperature (Larcher & Wagner 2010) and leaf temperature to become significantly greater than ambient air temperatures (Salisbury & Spomer 1964;Körner & Cochrane 1983). For example, in the cushion plant Silene acaulis, a maximum dif-ference of 22 (Neuner et al 2000) and 24.5 K (Gauslaa 1984) between leaf and ambient air temperatures was measured on calm summer days that were characterized by little wind and high solar irradiation.…”
Section: Introductionmentioning
confidence: 99%